Ten interleukins and risk of prostate cancer - Li, Bing-Hui; Yan, Si-Yu; Luo, Li-Sha; Zeng, Xian-Tao; Wang, Yong-Bo; Wang, Xing-Huan (Frontiers in Oncology, 2023)
Background Interleukins (ILs) have been reported to be related to prostate cancer. The aims of this study were to estimate the levels for several key interleukins in prostate cancer and the causal effects between them. Methods We conducted a bi-directional two-sample Mendelian randomization (MR) study to assess the causal associations between ILs and prostate cancer. Genetic instruments and summary-level data for 10 ILs were obtained from three genome-wide association meta-analyses. Prostate cancer related data were obtained from the PRACTICAL (79,148 cases and 61,106 controls), UK Biobank (7,691 cases and 169,762 controls) and FinnGen consortium (10,414 cases and 124,994 controls), respectively. Results The odds ratio of prostate cancer was 0.92 (95% confidence interval (CI), 0.89, 0.96; P=1.58×10-05) and 1.12 (95% CI, 1.07, 1.17; P=6.61×10-07) for one standard deviation increase in genetically predicted IL-1ra and IL-6 levels, respectively. Genetically predicted levels of IL-1ß, IL-2a, IL-6ra, IL-8, IL-16, IL-17, IL-18, and IL-27 were not associated with the risk of prostate cancer. Reverse MR analysis did not find the associations between genetic liability to prostate cancer and higher levels of IL-1ra (β, -0.005; 95% CI, -0.010, 0.001; P=0.111) and IL-6 (β, 0.002; 95% CI, -0.011, 0.014; P=0.755). Conclusion This MR study suggests that long-term IL-6 may increase the risk of prostate cancer and IL-1ra may reduce it.